Utility of admission cardiac troponin and "Ischemia Modified Albumin" measurements for rapid evaluation and rule out of suspected acute myocardial infarction in the emergency department. Issue 4 (20th March 2006) - Collinson, P O; Gaze, D C; Bainbridge, K; Morris, F; Morris, B; Price, A; Goodacre, S
Abstract : Objective: To assess if the combination of cardiac troponin (cTn) and Ischemia Modified Albumin (IMA) can be used for early exclusion of acute myocardial infarction (AMI). Methods: Prospective consecutive admissions to the emergency department (ED) with undifferentiated chest pain were assessed clinically and by electrocardiography. A total of 539 patients (335 men, 204 women; median age 51.9 years) considered at low risk of AMI had blood drawn on admission. If the first sample was less than 12 hours from onset of chest pain, a second sample was drawn two hours later, at least six hours from onset of chest pain. Creatine kinase MB isoenzyme (CKMB) mass was measured on the first sample and CKMB mass and cTnT on the second sample. An aliquot from the first available sample was frozen and subsequently analysed for IMA. If cTnT had not been measured on the original sample cTnI was measured (n = 189). Results: Complete data were available for 538/539 patients. IMA or cTn was elevated in the admission sample of all patients with a final diagnosis of AMI (n = 37) with IMA alone elevated in 2/37, cTn alone in 19/37, and both in 16/37. In 173/501 patients in whom AMI was excluded both tests were negative. In the non-AMI group 22 patients had elevation of both IMA and cTn in the initial sample, suggesting ischaemic disease. Conclusion: Admission measurement of cardiac troponin plus IMA can be used for early classification of patients presenting to the ED to assist in patient triage.